1982
DOI: 10.1111/j.1476-5381.1982.tb08751.x
|View full text |Cite
|
Sign up to set email alerts
|

J.H. Burn: an appreciation

Abstract: of Pharmacology at Oxford, died in his ninetieth year on July 13th, 1981.Those who worked with Harold Burn will always have their own vivid and very personal memories of him but there are hundreds of others who knew him personally, and thousands who did not, who will never forget this exceptional man. And there are perhaps tens of thousands, including those in future generations who will be influenced by what he was, by what he wrote and what he did. If anyone can be said to have moulded the subject of pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The development of quantitative bioassay by J.H. Burn (Vane, 1982 ) and the initiation of analytical pharmacology by H.O. Schild (Arunlakshana and Schild, 1959 ) paralleled studies reported above.…”
mentioning
confidence: 84%
“…The development of quantitative bioassay by J.H. Burn (Vane, 1982 ) and the initiation of analytical pharmacology by H.O. Schild (Arunlakshana and Schild, 1959 ) paralleled studies reported above.…”
mentioning
confidence: 84%
“…At the time, Burn’s laboratory had a superb reputation as a centre for pharmacological research in the United Kingdom and was the site where the Nobelist John Vane (1927–2004) developed his lifelong interest in pharmacology. 18…”
Section: The Exile Of Scientists Of Non-aryan Descentmentioning
confidence: 99%
“…On entering the Oxford Department of Pharmacology in 1964 as a rather naïve, newly minted Canadian Rhodes Scholar with a background in chemistry, I was only dimly aware of the rich pharmacology‐focused environment I had joined. The department shaped by W D M Paton, continuing in the directions set by his predecessor, J H Burn (Vane, ), accurately reflected Paton's own view of pharmacology in terms of its close relationship with chemistry and its ability to progress ‘from the molecular level to the whole man’ (Paton, ). Fortunately for me, Paton at that time also believed that the discipline was ‘not yet too sophisticated technically, and still young and fresh enough for the simpleminded to contribute’ (Paton, ).…”
Section: Introductionmentioning
confidence: 99%